2017
DOI: 10.1080/09712119.2017.1299014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maize DDGS addition on carcass and meat quality of lambs of native sheep breed

Abstract: The aim of the study was to characterize carcass and meat quality of lambs of native sheep breed, which were fed a diet containing maize dried distiller's grains with solubles (DDGS). The experiment involved 20 ram lambs of the native sheep breed Polish Heath Sheep (Wrzosówka sheep), which were selected from a conservation herd. The lambs received meadow hay and straw ad libitum as well as about 0.4 kg of concentrate per animal. The control group (C) received a standard diet based on cereal components and soyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
(14 reference statements)
3
7
0
Order By: Relevance
“…Compared with CON, the BYP concentrate contained less saturated FA (SFA; 36.0 vs. 25.4%, respectively). This is in agreement with previous studies in which diets including DDGS, DCP, or EOC were tested [8][9][10], and it was attributed to the high proportion of unsaturated FA in DDGS, DCP, and EOC [5,6,30].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Compared with CON, the BYP concentrate contained less saturated FA (SFA; 36.0 vs. 25.4%, respectively). This is in agreement with previous studies in which diets including DDGS, DCP, or EOC were tested [8][9][10], and it was attributed to the high proportion of unsaturated FA in DDGS, DCP, and EOC [5,6,30].…”
Section: Resultssupporting
confidence: 93%
“…Chemical composition of the meat was within the range reported by others [11,34,47,48] for lambs from different breeds slaughtered at similar body weight. Our results agree with those from other studies reporting that inclusion of corn DDGS [10], DCP [49], or EOC [50] in the concentrate for fattening lambs had no effects on chemical composition of meat. Some studies reported that the inclusion of corn DDGS in the diet of Rambouillet lambs (20% DDGS [51]) and Wrzosówka lambs (45% DDGS [10]) resulted in a more delicate texture.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Research on DDGS substituting traditional sources of protein and energy in feedlot lamb diets found no differences in major carcass traits ( Van Emon et al, 2012 ; Abdelrahim et al, 2014 ; Kawęcka et al 2018 ), which can be understood as an advantage to the sheep industry by reducing production costs without losing carcass grade ( Schauer et al 2008 ; Whitney and Braden, 2010 ; Crane et al, 2017 ). However, in agreement with this study, some authors ( Felix et al 2012 ; Curzaynz-Leyva et al 2019 ) have reported positive effects of DDGS levels on lamb carcass traits, which might be even more interesting for the sheep industry.…”
Section: Resultsmentioning
confidence: 99%